The Long-Term Effect of Blue-Light Blocking Spectacle Lenses on Adults’ Contrast Perception - Lian, Yan; Lu, Weiwei; Huang, Haixiao; Wu, Ge; Xu, Aiqin; Jin, Wanqing (Frontiers in Neuroscience, 2022)
Purpose To evaluate the long-term effect of two different degrees of blue-light blocking (BB) spectacle lenses on adults’ contrast perception under various lighting conditions. Methods In total, 144 healthy adults aged 24.70 (±4.32 years) were recruited to this randomized controlled trial. The participants were randomly divided into three groups and used three different spectacle lenses (15% BB: 15% blue-blocking spectacle lenses; 30% BB: 30% blue-blocking spectacle lenses; RC: regular clear lenses serving as control). Contrast sensitivity under four light conditions (scotopic and photopic, both with/without glare) was measured using standard clinical tests at baseline, 1 month, 3 months and 6 months of use. The area under the log contrast sensitivity function (AULCSF) was also computed as an index for their overall contrast sensitivity across spatial frequencies. Results There was no significant difference in AULCSFs among the three types of spectacle lenses under any light condition (all P > 0.81). No statistical difference was found in the AULSCF among the four time points (all P > 0.39), with no interaction between the effects of group and time (all P > 0.42). Conclusion Wearing blue-light blocking lens had no clinically significant effect on adults’ long-term contrast perception under scotopic or photopic conditions, or with glare.